Pelatihan Al-Banjari untuk Meningkatkan Semangat Kegiatan Rutinan Pembacaan Al-Barzanji Santri Pondok Pesantren Ar-Roudotussibyan Desa Cihanjawar - Ahmad Fajar; Riezal Mochammad Ramlie (Penerbit Widina, Widina Media Utama, 2023)
Al-Banjari music has become a highly popular art form among students at Pondok Kampung Gunung Bakti in Cihanjawar Village, Bojong District, Purwakarta Regency, especially at the Ar-Roudotussibyan Islamic Boarding School. Al-Banjari is often used as an accompaniment in activities such as reading al-barzanji, circumcision, wedding, or the birthday of Prophet Muhammad. However, the lack of understanding and skills in innovating rhythms and melodies make al-Banjari less effective and rarely used as an accompaniment. This problem is caused by the lack of special training accompanied by those who master the art of al-Banjari. The objective of this community service is to improve the understanding and creativity of students in using al-Banjari musical instrument and to increase their enthusiasm in routine activities such as reading al-barzanji at the Ar-Roudotussibyan Islamic Boarding School. The method used in this community service is special training and mentoring in playing the al-Banjari musical instrument. The training is conducted using appropriate teaching techniques to improve the understanding and skills of the students in playing the musical instrument. The al-Banjari training carried out in the community service activities at the Ar-Roudotussibyan Islamic Boarding School in 2023 succeeded in improving the understanding and skills of the students in using and playing the al-Banjari. In addition, the enthusiasm of the students in routine activities such as reading al-barzanji also increased after the training.